Application of exosomes in tumor immunity: recent progresses - Qiu, Haiyan; Liang, Junting; Yang, Guang; Xie, Zhenyu; Wang, Zhenpeng; Wang, Liyan; Zhang, Jingying; Nanda, Himansu Sekhar; Zhou, Hui; Huang, Yong; Peng, Xinsheng; Lu, Chengyu; et al. (Frontiers in Cell and Developmental Biology, 2024)
Exosomes are small extracellular vesicles secreted by cells, ranging in size from 30 to 150 nm. They contain proteins, nucleic acids, lipids, and other bioactive molecules, which play a crucial role in intercellular communication and material transfer. In tumor immunity, exosomes present various functions while the following two are of great importance: regulating the immune response and serving as delivery carriers. This review starts with the introduction of the formation, compositions, functions, isolation, characterization, and applications of exosomes, and subsequently discusses the current status of exosomes in tumor immunotherapy, and the recent applications of exosome-based tumor immunity regulation and antitumor drug delivery. Finally, current challenge and future prospects are proposed and hope to demonstrate inspiration for targeted readers in the field.